Respuesta :
Answer:
C
Step-by-step explanation:
Tomas learned that
[tex]a^3+b^3=(a+b)(a^2-ab+b^2)[/tex]
If [tex]a=2x,\ b=y[/tex], then
[tex]a^3+b^3\\ \\=(2x)^3+y^3\\ \\=((2x)+y)((2x)^2-(2x)y+y^2)\\ \\=(2x+y)(4x^2-2xy+y^2)[/tex]
The product that Tomas should choose is [tex](2x+y)(4x^2-2xy+y^2)\\[/tex]
How to find the difference of cubes
Given the expression
[tex]a^3+b^3=(a+b)(a^2-ab+b^2)[/tex]
Given the following parameters
a = 2x
b = y
Substitute into the expression to have:
[tex](2x)^3+y^3=(2x+y)((2x)^2-2xy+y^2)\\[/tex]
[tex](2x)^3+y^3=(2x+y)(4x^2-2xy+y^2)\\[/tex]
Hence the product that Tomas should choose is [tex](2x+y)(4x^2-2xy+y^2)\\[/tex]
Learn more on difference of cubes here: https://brainly.com/question/2747971